Effects of Barium Sulphate on Thermal Behaviour of Poly(L-lactic Acid) - Cai, Yan-Hua (Asian Journal of Chemistry, 2012)
Poly(L-lactic acid)(PLLA)/barium sulphate (BaSO4) composites were fabricated by melt blending and hot-press forming process. The thermal behaviour of PLLA/BaSO4 composites with different amount of BaSO4 has been investigated by differential scanning calorimetry (DSC), polarized optical microscopy (POM) and thermogravimetric analysis (TGA). Barium sulphate is effective nucleating agent for the crystallization and can increase the overall crystallization rate of PLLA. With the addition of 2 % BaSO4, the crystallization temperature (To) increase from 105.88- 117.03 ºC and the crystallization enthalpy (DHc) increase from 1.379-39.39 J g-1. Polarized optical microscopy shows that BaSO4 makes the spherulite size decrease dramatically and the spherulite number become large. With increasing of cooling rate, the crystallization peak of PLLA/BaSO4 shifts to lower temperature and the crystallization peak becomes wider. TGA analysis shows that the decomposition temperature of PLLA/BaSO4 composites is slightly higher than that of neat PLLA.